Review of the Lake Malaŵi genus Melanochromis (Teleostei: Cichlidae) with a description of a new species - Konings, Adrianus F.; Stauffer, Jr., Jay R. (Zootaxa, 2012)
The Lake Malaŵi genus Melanochromis included five species at its inception and was originally distinguished fromPseudotropheus on the basis of morphology, including the arrangement of teeth on the lower pharyngeal bone. Thediagnosis has been extended twice, first to include all elongate mbuna that possess horizontal stripes and U-shaped toothbands and later to exclude mbuna that do not exhibit a sex-related reversal in their colour pattern. Recently, the diagnosisof the genus was refined on the basis of the melanin pattern. The genus now includes only species with a basic melaninpattern, which consists of two black horizontal lateral stripes on a light background. Most adult members of the genus,thus defined, have a sex-related reversal of pigmentation pattern. Here we describe Melanochromis mpoto n. sp. from thenorthwestern part of Lake Malawi, synonymize M. parallelus Burgess & Axelrod 1976 with M. loriae Johnson 1975,redescribe M. chipokae Johnson 1975 and M. robustus Johnson 1985, and reclassify and designate a lectotype for M. brevis Trewavas, 1935.